Approximation of fixed point of generalized non-expansive mapping via new faster iterative scheme in metric domain - Muhammad, Noor; Asghar, Ali; Irum, Samina; Akgul, Ali; Khalil, E. M.; İnç, Mustafa (Amer Inst Mathematical Sciences-Aims, 2023)
In this paper, we establish a new iterative process for approximation of fixed points for contraction mappings in closed, convex metric space. We conclude that our iterative method is more accurate and has very fast results from previous remarkable iteration methods like Picard-S, Thakur new, Vatan Two-step and K-iterative process for contraction. Stability of our iteration method and data dependent results for contraction mappings are exact, correspondingly on testing our iterative method is advanced. Finally, we prove enquiring results for some weak and strong convergence theorems of a sequence which is generated from a new iterative method, Suzuki generalized non-expansive mappings with condition (C) in uniform convexity of metric space. Our results are addition, enlargement over and above generalization for some well-known conclusions with literature for theory of fixed point.
Keywords: Suzuki generalized non expansive mapping; uniformly convex metric space; iteration process; weak convergence; strong convergence; condition (C)